The Search of a Lithuanian Town Spirit: The Phenomenon of the TV Series Cycle “Our Towns” - Šermukšnytė, Rūta (Lietuvos istorijos studijos, 2017)
This article analyzes the Lithuanian national TV series cycle Our Towns for the first time in Lithuanian historiography. The research object was chosen because of the phenomenon of this TV series in the context of Lithuanian audiovisual historical culture. This TV series, which has been on the air for more than 25 years, has received considerable resonance in the public and is to be regarded as a kind of visual “Encyclopedia” of Lithuanian towns – the focus of which has always been (and still is) the disclosure of the current situation of culture, natural diversity and historical identity of Lithuanian towns. This article aims to reveal the phenomenon of the content of TV series cycle, showing its versatility to deny its assessments which are very much one-sided. The following issues are essential: How the spirit of a town is perceived in this TV series cycle? Who are considered to be the “bearers” of a small-town spirit? What events, individuals, social groups, and other relevant elements construct the past of a town? This article reveals that the spirit of towns in the Our Towns TV series is related to the pre-Soviet past or the tradition that testifies the continuity of this past. In Our Towns, the main “bearers” of a former place of spirit are the old dwellers of towns or their offspring, those who took over the values and traditions of their predecessors. The recording and showing of their memories – which form the core of these TV series – is perhaps the biggest element of value in Our Towns. The similarity of towns pasts suggests the notion of a unique place for us, which is close to the concept generated by the creators of this TV cycle – the towns are unique because they are our own, inherited, close to heart and identifiable. This feeling of commonality, similarity and identity perhaps is the reason why so many people like to watch the Our Towns TV series.